2019
DOI: 10.21474/ijar01/9976
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Performance Mediates Between Iconic Product Innovation and Sustainable Competitive Advantages

Abstract: Companies that carry out continuous innovation are seen as a source of competitive advantage. In achieving competitive advantage, there are several other things that can be a measure, namely resource excellence, position advantage, and value advantage for customers. The superiority of resources consists of superior expertise and excellence in raw materials as well as marketing and capital performance. The position superiority which consists of relatively low of cost advantages and value advantages for customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Thus, the results of this study are not confirmed to the empirical findings ofPrajogo (2016),Aksoy (2017),Fatach & Nursyamsiah (2019),Zaefarian, Forkmann, &Mitrega (2017), andSharma, Davcik, &Pillai (2016) that innovation products made can improve business performance in SMEs.Further findings conveyed, that product innovation can determine business performance if it is mediated by competitive advantage. The results of this study are following the findings ofAstrid (2017) andMuh, Rahman, Syamsu, and Madris (2019), that product innovation as a source of competitive advantage can improve business performance.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Thus, the results of this study are not confirmed to the empirical findings ofPrajogo (2016),Aksoy (2017),Fatach & Nursyamsiah (2019),Zaefarian, Forkmann, &Mitrega (2017), andSharma, Davcik, &Pillai (2016) that innovation products made can improve business performance in SMEs.Further findings conveyed, that product innovation can determine business performance if it is mediated by competitive advantage. The results of this study are following the findings ofAstrid (2017) andMuh, Rahman, Syamsu, and Madris (2019), that product innovation as a source of competitive advantage can improve business performance.…”
supporting
confidence: 82%
“…The research results obtained are in line with the findings of Narida, Sastrya, & Achmadi (2021) that product innovation carried out by SME actors does not necessarily have a direct impact on business achievement. This makes it possible, the product innovation carried out is a process in business activities that aims to increase the added value and competitiveness of the products produced(Muh, Rahman, Syamsu, and Madris (2019). Thus, the results of this study are not confirmed to the empirical findings ofPrajogo (2016),Aksoy (2017),Fatach & Nursyamsiah (2019),Zaefarian, Forkmann, &Mitrega (2017), andSharma, Davcik, &Pillai (2016) that innovation products made can improve business performance in SMEs.Further findings conveyed, that product innovation can determine business performance if it is mediated by competitive advantage.…”
mentioning
confidence: 57%
See 1 more Smart Citation